Associations of collegiate football career and incident concussion with players' health: a longitudinal study from the CARE Consortium - Hunzinger, K. J.; Caccese, J. B.; Law, C. A.; Wittmer, R. M.; Buckley, T. A.; Broglio, S. P.; McAllister, T. W.; McCrea, M. A.; Pasquina, P. F.; Schneider, A. L. C.; CARE Consortium Investigators (Sports Medicine, 2025)
Background: The influence of repetitive head impacts on collegiate football players remains unclear as prior research is often limited to small samples or short-term studies focused on single seasons. Objective: Our objective was to determine the associations between collegiate football career or incident concussion and changes in neurocognitive function, postural stability, and physical and psychological health. Methods: In total, 574 football players enrolled in the Grand Alliance Concussion Assessment, Research and Education (CARE) Consortium (median age 18.0 years [interquartile range 18.0-19.0], 52% white race, 26% with incident concussion) completed baseline and exit evaluations (i.e., beginning and end of collegiate career) consisting of neurocognitive, postural stability, and physical/psychological health assessments, specifically, Immediate Post-Concussion Assessment and Cognitive Testing, Standardized Assessment of Concussion, Balance Error Scoring System, Sport Concussion Assessment Tool-5 (SCAT-5) Symptom checklist, and the Brief Symptom Inventory-18. Adjusted linear regression models incorporating inverse probability of attrition weighting were used to compare changes in scores between baseline and exit evaluations overall and by incident concussion status. Results: Overall, athletes had small improvements in neurocognitive functioning and postural stability over time but had small increases in symptom severity. Both the incident concussion and no incident concussion groups improved similarly on neurocognitive and postural stability measures (all p > 0.05 for difference in change over time between incident concussion groups). Individuals with incident concussion reported fewer symptoms and lower symptom severity over time than did those without incident concussion (SCAT symptom count difference - 1.22; 95% confidence interval [CI] - 1.89 to - 0.54; SCAT symptom severity difference: - 2.46; 95% CI - 4.06 to - 0.86; Brief Symptom Inventory-18 somatization difference: - 0.55; 95% CI - 0.93 to - 0.17). Conclusions: Overall, collegiate football players demonstrated small, non-clinically meaningful improvements in neurocognitive function and postural stability. Moreover, athletes who experienced a concussion reported slight improvements in physical/psychological health symptoms over their collegiate careers.